Fluorination effects of A-D-A-type small molecules on physical property and the performance of organic solar cell - Chen, Ko-Wei; Lin, Li-Yen; Li, Yi-Hua; Li, Ya-Ze; Nguyen, Thanh Phuc; Biring, Sajal; Liu, Shun-Wei; Wong, Ken-Tsung (Organic electronics, 2018)
Four new molecules with acceptor-donor-acceptor (A-D-A) configuration where cyclopenta[2,1-b:3,4-b′]dithiophene (CPDT) as the electron-donating core connecting to cyano(CN)-substituted 2,1,3-benzothiaidiazole (BT) as electron-withdrawing end groups are reported. With the same acceptor CN-BT, we found that CPDT can serve as a better donor as compared to that of dithieno[3, 2-b: 2′, 3′-d]silole (DTS) to give stronger intramolecular charge transfer (ICT) character and therefore better light harvesting ability. The number and orientation of F-substitution on the BT ring, giving a clear structure-property relationship, can subtly manipulate the physical characteristics. These A-D-A type molecules were employed as electron donor in conjunction with C70 as the electron acceptor in vacuum-deposited bulk heterojunction (BHJ) small-molecule organic solar cells (SMOSCs). Among them, the device based on CBCIF containing BT ring with one F group directing toward the CPDT core gave the best device performance with a power conversion efficiency of 4.94% with Jsc of 10.16 mAcm−2, Voc of 0.98 V, fill factor (FF) of 0.50. The superior device characteristics were attributed to the suitable morphology of the donor/C70 film. New small molecule donor employing bridge atom and F-substitution effects improves the power conversion efficiency in vacuum-deposited organic solar cell. [Display omitted] •Four cyclopentadithiophene (CPDT)-centered A-D-A-type molecules with CN-substituted benzothiaidiazole (BT) were reported.•The number and orientation of F-substitution introduced on the BT ring can subtly manipulate the physical characteristics.•These A-D-A type molecules together with C70 were used as active layer in small-molecule organic solar cells (SMOSCs).•The donor CBCIF with one F group on BT ring directing toward the CPDT core gave the best device efficiency of 4.94%.